BENDING STRENGTH OF T-SHAPE CORNER DETACHABLE JOINTS OF STRUCTURAL ELEMENTS MADE OF PLYWOOD - Simeonova, Ralitsa (Innovation in Woodworking Industry and Engineering design, 2016)
In this study are given the results from investigation on bending strength of T-shape corner detachable joints of structural elements made of plywood. It has been established the bending moment under compression bending test. The highest bending strength were achieved with screw with cross dowel and Confirmat ∅7 x 70 and ∅7 x 50 mm and lowest bending strength have joints with bolt and nut and two types of eccentric connectors.It is recommended that the comparative data of bending strength is taken into consideration when the designers and engineers have to choose the type of joints in the furniture constructions.